Serum level of substance P in patients with lung injuries due to sulfur mustard - Najafian, Bita (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Chronic bronchiolitis is the most important problems of chemical victims of mustard gas. Diverse studies suggest that substance P (SP) as a member of tachykinin neuropeptides, has a significant role in the neurogenic inflammation processes of the airways and lungs. We aimed to determine the serum level of SP in chemical victims of mustard gas and compare it with normal subjects. MATERIALS AND METHODS: The chemical victims were divided into the 2 groups of 30:A group with mild to moderate pulmonary symptoms and other group with moderate to severe symptoms and compared with 3(rd) group as healthy controls. After preparing our samples and using the SP kit, final analysis was performed with enzyme-linked immunosorbent assay reader. RESULTS: The Concentration of circulatory SP levels in the chemical patients was 2.86 ± 1.47 ng/ml and had not a significant difference with the control group (3.15 ± 1.03 ng/ml) (P > 0.05). The circulatory SP levels were 2.48 ± 0.92 ng/ml and 3.28 ± 1.73 ng/ml in patients with moderate to severe symptoms and mild to moderates (P < 0.05) respectively. CONCLUSION: The SP may have a role in pulmonary complications of mustard gas. The lower level of SP in the moderate to severe patients may be due to corticosteroid consumption in such severe cases. However, further studies are needed to clarify the roles and mechanism of SP in this setting.